Prevalence and Risk Factors of Feline Immunodeficiency Virus and Feline Leukemia Virus Infection in Healthy Cats in Thailand - Sprißler, Fabienne; Jongwattanapisan, Prapaporn; Luengyosluechakul, Supol; Pusoonthornthum, Rosama; Reese, Sven; Bergmann, Michèle; Hartmann, Katrin (Frontiers in Veterinary Science, 2022)
Infections with feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) occur worldwide and are among the most important infectious diseases in cats. The aim of the present study was to determine the prevalence of FIV and FeLV infection in healthy outdoor cats in North, Northeast and Central Thailand. So far, a study on retrovirus prevalence of healthy cats in Thailand in a larger geographic area has not been published yet. In addition, risk factors for FIV and FeLV infections were evaluated. Two hundred sixty healthy cats were prospectively recruited. They originated from 13 locations in North, Northeast, and Central Thailand and were presented for either preventive health care and/or neutering. In each cat, a physical examination was performed to confirm health status. FIV and FeLV status was determined using a commercial rapid enzyme-linked immunosorbent assay (ELISA) (SNAP Combo Plus FeLV/FIV, IDEXX). Risk factors were analyzed by binary logistic regression analysis. Samples of 15/260 (5.8%) cats were positive for FIV antibodies, and 11/260 (4.2%) samples were positive for FeLV antigen. One of the 260 (0.4%) cats was positive for both, FIV and FeLV infection. In binary logistic regression analysis, no parameter was associated with a higher risk for FeLV infection. However, cats had a significantly (p = 0.025) higher risk for FIV infection when they were 2 years or older. FIV and FeLV infections occur in healthy cats in North, Northeast and Central Thailand, but prevalence was lower than expected. No risk factors for FeLV infection were detected, but risk for FIV infection increases with age.